Analisis Pengelolaan Dan Pemanfaatan Dana Desa Di Kecamatan Damau Kabupaten Kepulauan Talaud - Salindeho, Mariam Magdalena; Kalangi, Lintje; Warongan, Jessy (Universitas Sam Ratulangi, 2017)
Abstract. This study aims to analyze the Management and Utilization of Village Funds in District Damau Talaud Islands. This is a qualitative exploratory research. Data were obtained by in-depth interviews, observation and documentation study. Key informants were determined by purposive sampling to obtain correct and accurate information. Informants are Village Devices, Village Assistants, Religious Leaders and Customary People. Interviews were conducted by semi-structured in-depth interviews for about 45 to 60 minutes. The triangulation method was used in testing the validity or credibility of data and data sources. Interviews were transcribed into data transcriptions. The results of the interpretation are summarized in the narrative text. The results indicate that the management and utilization of village funds (starting from their planning, executing, administrating and responsibility) are conducted in accordance with Permendagri Number 113 year 2014. This research also found that there are several obstacles in the Management and Utilization of Village Funds in District Damau, for instance the regulations obstruct structure bureaucracy. Those regulations governing the planning process do not match the basic needs of the existing priorities in the village. Other obstacles are limited knowledge and understanding of human resources, ineffective communication between the village head and other village apparatus or between the village head and the community. It is thus the Permendesa must be in accordance with the situation and conditions in the village, so that the planning process can answer the basic needs of the priorities in the village. In addition, guidance and supervision from local government should be more effective including local government should conduct socialization and guide the village treasurer to understand SISKEUDES sufficiently.Keywords: Management of Village Funds, Benefit of Village Funds, Village Fund Issues.Abstrak. Dalam penelitian ini bertujuan menganalisis Pengelolaan Dan Pemanfaatan Dana Desa Di Kecamatan Damau Kabupaten Kepulauan Talaud. Penelitian ini adalah penelitian kualitatif dengan pendekatan eksploratif. Data diperoleh melalui teknik wawancara mendalam dan studi dokumentasi. Informan kunci ditentukan secara purposive sampling untuk mendapatkan hasil informasi yang tepat dan akurat. Para informan adalah Perangkat Desa, Pendamping Desa dan Tokoh Agama. Wawancara menggunakan In-depth interview jenis semi terstruktur selama 45 hingga 60 menit. Metode triangulasi digunakan dalam pengujian validitas atau kredibilitas data dan sumber data. Hasil interpretasi disimpulkan dalam teks naratif. Hasil penelitian menunjukkan bahwa dalam proses pengelolaan dan pemanfaatan Dana Desa mulai dari perencanaan, pelaksanaan, penatausahaan, pelaporan dan pertanggungjawaban sudah mengacu pada Permendagri Nomor 113 Tahun 2014. Penelitian ini juga menemukan beberapa hambatan dalam pengelolaan dan pemanfaatan dana desa, misalnya regulasi yang menyebabkan hambatan dalam struktur birokrasi. Regulasi yang mengatur pada proses perencanaan tidak sesuai dengan kebutuhan dasar prioritas yang ada di desa. Hambatan lainnya adalah keterbatasan pengetahuan dan pemahaman sumber daya manusia, komunikasi yang tidak efektif antara kepala desa dengan perangkat desa lainnya maupun antara kepala desa dengan masyarakat. Dengan demikian seharusnya regulasi turun sebelum dilaksanakannya musrembang desa sehingga pada saat usulan sampai pada penetapan APBDesa sesuai dengan situasi dan kondisi yang ada di desa supaya proses perencanaan dapat menjawab kebutuhan dasar prioritas di desa. Pembinaan dan pengawasan dari pemerintah daerah juga harus lebih efektif serta pemerintah daerah harus mengadakan sosialisasi dan bimbingan kepada bendahara desa tentang SISKEUDES.Kata Kunci: Pengelolaan Dana Desa, Manfaat Dana Desa, Hambatan Dana Desa.Â